Contribution of electro-optics effect on canola oil as a new alternative method for determination of oil quality using transmission and fluorescence polarization. (May 2019) - Afiefah, I; Azam, M; Sugito, H; Firdausi, K S
Abstract: In this paper we studied contribution of electro-optics effect for evaluation of canola oil quality using transmission and fluorescence polarization. The samples were two different quality of canola oils, i.e. edible canola and expired canola based on the date of expiration at the time of measurement. The physical variable of polarization angle was measured using a pair of polarizers from a 532 nm of green pointer laser. The electro-optics effect was produced by applying high DC voltage 0-9 kV on samples. The result shows that the change of polarization angle of expired oil is greater than the good one for both transmission and fluorescence. The increasing polarization angle is accompanied by increasing saturated FAs and decreasing polyunsaturated FAs simultaneously, in agreement with our previous reports.The fluorescence polarization is dependent on the polarizer's angle of incoming light and has average angle greater than transmission light. The electro-optic fluorescence is twice as electro-optics transmission due to possibly coupling between pure scattering and fluorescence together, in which large size of TG molecules play an important role into the light scattering and fluorescence perpendicular to the incoming light.This fluorescence light method provides more accurate measurement that transmission light and seems powerful comparison to the other spectroscopy methods.